2010
DOI: 10.1088/1742-6596/234/2/022039
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Doping of Tin-oxides pinning centers into YBCO films by MOD method

Abstract: Abstract. Tin-oxides were doped into YBCO films as pinning centers to improve J C properties in a magnetic field. YBCO films were grown by a metal organic deposition process using trifluoroacetates starting solutions which contains tin compounds such as SnO 2 particles or tinacetylacetonate salts for pinning centers. J c of the YBCO films were enhanced by introducing pinning centers both SnO 2 and tin-acetylacetonates in the wide range of the magnetic angle. Especially, J C of YBCO film grown by the solution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These peaks were controversially indexed. While some groups assigned these peaks to BaSnO 2 [19,22], Choi et al indicate that these peaks belong to Y-Ba-Sn-O [18]. However, it can be concluded that Sn was not incorporated into the Y-123 crystal, and instead participated in the form of Sn-based secondary phases.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks were controversially indexed. While some groups assigned these peaks to BaSnO 2 [19,22], Choi et al indicate that these peaks belong to Y-Ba-Sn-O [18]. However, it can be concluded that Sn was not incorporated into the Y-123 crystal, and instead participated in the form of Sn-based secondary phases.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many oxides, including RE 2 O 3 (RE: Y, Dy, and Ho) [19][20][21], perovskite BZO [22][23][24][25][26][27][28][29][30], BSO [31][32][33][34][35], BaHfO 3 [36], cubic-double-perovskite Ba 2 YTaO 6 [37] and YBa 2 SnO 5.5 [38], have also been incorporated into the YBCO and REBCO (RE: Sm, and Gd) matrix by the MOD process. Unlike nano-structured columnar defects in PLD-processed YBCO or REBCO films except RE 2 O 3 , all the above oxides formed point-like nanoparticles in MOD-processed YBCO films.…”
Section: Introductionmentioning
confidence: 99%